PEMERTAHANAN BAHASA BUGIS DI KOTA AMBON [Bugis Language Defence in the city of Ambon] - Erniati Erniati (Kantor Bahasa Provinsi Maluku, 2018)
This study examines the maintenance of Bugis language in the Wara neighborhood, Ambon City. As a language brought by immigrants from South Sulawesi, the Bugis language is a minority language that is in the midst of the majority language, namely Ambonese Malay. According to experts that the existence of minority languages in an area will melt into the majority language but in fact the Bugis language remains used in daily communication among ethnic groups. The research problem is how is the defense of Bugis language in Ambon and what factors support this achievement. The purpose of this study was to see how far the Bugis language was preserved in Ambon City and what factors supported the defense. This study uses the method of observation and interviews with respondents. The results showed that the Bugis ethnic community in Ambon City, especially Bugis who lived in the Wara environment still used Bugis language in the family realm, the realm of neighboring, the realm of work, the realm of education, and the realm of religion. Factors of loyalty of speakers and Bugis ethnic community organizations are the things that most support the defense of Bugis in Ambon City, especially in the Wara Neighborhood.Kajian ini meneliti tentang pemertahanan bahasa Bugis di Lingkungan Wara, Kota Ambon. Sebagai bahasa yang dibawa oleh pendatang dari Sulawesi Selatan, bahasa Bugis merupakan bahasa minoritas yang berada di tengah-tengah bahasa mayoritas, yakni bahasa Melayu Ambon.menurut para ahli bahwa keberadaan bahasa minoritas di suatu daerah akan lebur ke dalam bahasa mayoritas namun kenyatannya bahasa Bugis tetap digunakan dalam komunikasi sehari-hari di antara sesama etnis. Masalah penelitian adalah bagaimanakah pemertahanan bahasa Bugis di Ambon dan factor-faktor apakah yang mendukung pemerthanan tersebut. Tujuan penelitian ini adalah untuk melihat sejauhmana pemertahanan bahasa Bugis di Kota Ambon dan factor-faktor apa yang mendukung pemertahanan tersebut. Penelitian ini menggunakan metode observasi dan wawancara terhadap responden. Hasil penelitian menunjukan bahwa masyarakat etnis Bugis di Kota Ambon, khususnya etnis Bugis yang tinggal di Lingkungan Wara masih menggunakan bahasa Bugis pada ranah keluarga, ranah ketetanggaan, ranah pekerjaan, ranah pendidikan, dan ranah agama. Factor loyalitas penutur dan organisasi masyrakat etnis Bugis merupakan hal yang paling mendukung pemertahanan bahasa Bugis di Kota Ambon, khususnya di Lingkungan Wara.